The development of ovine placental lactogen deficient pregnancies - Baker, Callie M., author; Anthony, Russell V., advisor; Winger, Quinton A., committee member; Curthoys, Norman, committee member (Colorado State University. Libraries, 2014)
Intrauterine growth restriction (IUGR) results in significant fetal and neonatal mortalities and morbidities. Additionally, infants surviving IUGR experience increased incidence of heart disease, diabetes, hypertension and stroke during adulthood. A major placental secretory product, placental lactogen (PL), is found at high levels in maternal and fetal circulation, and is significantly reduced in both human and sheep IUGR pregnancies. While the exact function of PL has not been defined for any species, it is thought to modulate the mobilization of maternal nutrients to the fetus. Recently, the development of lentiviral-mediated expression of short hairpin RNA (shRNA) within sheep conceptuses has provided a means of examining placental gene function in sheep. The objective of this research was to generate ovine PL (oPL) deficient sheep pregnancies using lentivirus targeting the degradation of oPL mRNA, in order to assess the function of PL during pregnancy. We hypothesize that oPL deficiency during pregnancy will lead to IUGR near term. To test our hypothesis a preliminary study was conducted to evaluate the in vivo efficacy of lentiviral-oPL targeting vectors in the sheep placenta at 55 days gestational age (dGA). Efficiency of oPLmRNA degradation was first measured in vitro using twelve promoter-targeting sequence combinations, tested in three cell lines overexpressing oPL. Two oPL target sequences (tg2 and tg6) were used, as either shRNA or shRNAmiR (microRNA mimic) sequences. Subsequently, three lentiviral constructs; hLL3.7 tg6 (human U6 promoter expressing oPL tg6 shRNA), hEF-1 tg2 (human elongation factor-1α promoter expressing oPL tg 2 shRNAmiR) and oPGK tg6 (ovine phosphoglycerate kinase-1 promoter expressing oPL tg 6 shRNAmiR), were selected to be tested in vivo. Day 9 blastocysts were harvested from naturally mated donor ewes, infected with one of the lentiviral constructs, and 2 to 3 blastocysts were surgically transferred to recipient ewes. At 55 dGA, uterine vein (UtV) blood and placental tissues were collected for analysis of oPL expression, and compared to naturally mated controls (NMC). Based on a 95% confidence interval created from UtV oPL concentrations in NMC pregnancies (n=4), 3 out of 4 hLL3.7 tg6 pregnancies, 3 out of 4 hEF tg2 pregnancies and 4 out of 4 oPGK tg6 pregnancies were classified as responder pregnancies. Compared to NMC pregnancies, UtV oPL concentrations were significantly reduced (P≤0.05) in responder pregnancies. While we hypothesized that oPL deficiency will result in IUGR near-term, at 55 dGA there were no differences in fetal weights. To test our overall hypothesis, we generated 8 hEF-1-SC (human elongation factor-1α promoter expressing scrambled control shRNAmiR), 9 hEF-1 tg2, 7 hEF-1 tg6 (human elongation factor-1α promoter expressing oPL tg6 shRNAmiR) and 9 hLL3.7 tg6 singleton pregnancies that were harvested at 135 dGA. Based on two standard deviations below the mean placental weight of the hEF-1 SC pregnancies, 2 out of 7 hEF-1 tg6 pregnancies and 6 out of 9 hLL3.7 tg6 pregnancies were classified as tg6 responder pregnancies (tg6). Tg6 pregnancies resulted in significantly decreased (P≤0.05) oPL mRNA concentrations, placental weight and fetal body weight compared to the controls at 135 days of gestation. These data confirm the effect of lentiviral-oPL targeting vectors and suggest that oPL plays a significant role in early placental development. Interestingly, we also observed that tg6 pregnancies had significantly increased (P≤0.05) placental efficiency relative to controls, which may function as a coping mechanism to maintain pregnancy in the face of oPL deficiency. Uterine artery to uterine vein glucose gradients were also increased (P≤0.05) in tg6 pregnancies compared to controls, which may be indicative of increased glucose uptake by the placenta in order to maintain function. Further analysis revealed that circulating fetal insulin tended to be decreased in the umbilical artery (P≤0.10) of tg6 fetuses relative to control fetuses, thus supporting a role for oPL in altering fetal insulin production. Finally, mRNA concentrations of insulin-like growth factors (IGF) -I and -II, and insulin-like growth factor binding proteins (IGFBP) -2 and -3 were significantly reduced (P≤0.05) in fetal liver tissue of tg6 fetuses compared to the controls. While this could be an indirect result of IUGR, oPL may well induce the expression of fetal insulin-like growth factors during in utero development. Based on these results, our hypothesis that oPL deficiency during gestation would result in intrauterine growth restriction appears correct. Surprisingly, it appears that oPL may have its greatest impact during early pregnancy when the placenta is developing, however the presence of adequate oPL is likely to be important throughout gestation for healthy fetal growth.
Keywords: ovine; pregnancy; placental lactogen; IUGR; lentivirus; placenta